ANALYSIS OF THE PERFORMANCE OF PIKO HYDRO TURBINE ACRHIMEDES POWER PLANT ON THE EFFECT OF WATER PRESSURE (DINAMIS, 2024)
Turbines are the most important component in Pikohidro Power Plant (PLTPH). The turbine used in this PLTPH modeling is the Archimedes screw turbine. This Archimedes screw turbine is still very rare to use in the city of Pontianak. This study aims to make it easier to conduct tests related to parameters that affect the performance of the Archimedes screw turbine, one of which is the influence of water pressure. This study will discuss the influence of water pressure on the rotation produced by the Archimedes screw turbine so that it can be seen the voltage, current, power generated by the generator, in PLTPH modeling. The change in water pressure given is 3 psi, 4 psi, 5 psi. The results showed that the increase in water pressure given caused the performance of PLTPH to increase, where the highest efficiency was obtained at a pressure of 5 psi and the lowest efficiency was obtained at a pressure of 3 psi.Keywordsâ€” , PLTPH, Archimedes Turbine and Screw,Water Pressure